Temperature-Dependent Residue Depletion Regularities of Tiamulin in Nile Tilapia (Oreochromis niloticus) Following Multiple Oral Administrations - Cao, Cuiyv; Liu, Yongtao; Zhang, Guodong; Dong, Jing; Xu, Ning; Zhou, Shun; Yang, Yibin; Yang, Qiuhong; Ai, Xiaohui (Frontiers in Veterinary Science, 2021)
The aim of this study was to investigate the effect of different water temperatures (19℃, 25℃ and 30℃) on tissue residue depletion of tiamulin in Nile tilapia (Oreochromis niloticus) after 5 consecutive days of oral administration at the dose of 20 mg/kg body weight, and to calculate the corresponding elimination half-life (T1/2) and withdrawal times (WT). After oral administration at scheduled 11 time points (1, 2, 3, 5, 7, 9, 12, 15, 20, 25 and 30 days), samples of plasma and tissues (muscle plus skin, liver, kidney and gill) were collected. Tiamulin concentration in samples were determined by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). T1/2 was calculated by the equation: T1/2 = ln2/k. WT 1.4 software were carried out to calculate WT. The results showed that tiamulin was widely distributed in all tissue samples with the highest concentration in liver. At three different water temperature, the T1/2 were calculated as 2.76, 2.13, 1.64 day in plasma, 2.71, 1.85, 1.31 day in muscle plus skin, 2.27, 1.70, 1.50 day in liver, 2.84, 2.32, 1.94 day in kidney and 3.16, 2.42, 1.74 day in gill, respectively. At 19°C, the order of WT is kidney (11.88 d)>liver (10.41 d)>gill (10.77 d)>plasma (8.83 d)>muscle plus skin (7.14 d). The WT for tiamulin at 25°C was in the following order: kidney (8.40 d)>liver (8.21d)>gill (8.07 d)>plasma (7.24 d)>muscle plus skin (4.05 d). At 30 °C, the WT dropped and shown as follows: gill (6.99 d)>kidney (6.51 d)>liver (6.29 d)>plasma (3.27 d)>muscle plus skin (2.92 d). The present investigations indicated that increasing the temperature from 19°C to 30°C shortened T1/2 and WT of tiamulin in tilapia. To ensure the safety of fish consumption, the longest WT of tissues is suggested for tiamulin in Nile tilapia at corresponding water temperature, i.e. WT were 12 days at 19°C, 9 days at 25°C and 7 days at 30°C, respectively. Overall, our work with a view to provide theoretical basis of tissue residue depletion kinetics of tiamulin in fish, and improve us understanding the influence of the temperature on tissue residue depletion kinetics of tiamulin in fish.